2001
DOI: 10.1080/095003401750051442
|View full text |Cite
|
Sign up to set email alerts
|

Isochromatics demodulation from a single image using the regularized phase tracking technique

Abstract: In this work we propose a robust fringe demodulation technique applied to the analysis of a single isochromatics fringe pattern produced in photoelasticity. The method used is a regularized phase tracking algorithm with a new sequential scanning technique speci cally adapted for the characteristics of the isochromatic fringe patterns: possible apparition of closed fringes, large dynamic range in its spatial frequency content and low noise. The performance of the method is discussed and experimental results are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…There have been several attempts to evaluate the total fringe order using a single isochromatic image with monochrome, tricolour, or white light as source of illumination. Servin and Quiroga [69] used a single monochrome bright field image to obtain unwrapped isochromatics, by applying a RPT with a three-level quality map. Yoneyama et al [70] developed a tricolour photoelastic system for the evaluation of isoclinic and isochromatic parameters using a single tricolour image; however, they reported that the methodology lacked repeatability.…”
Section: Total Fringe Order Evaluation Using a Single Imagementioning
confidence: 99%
“…There have been several attempts to evaluate the total fringe order using a single isochromatic image with monochrome, tricolour, or white light as source of illumination. Servin and Quiroga [69] used a single monochrome bright field image to obtain unwrapped isochromatics, by applying a RPT with a three-level quality map. Yoneyama et al [70] developed a tricolour photoelastic system for the evaluation of isoclinic and isochromatic parameters using a single tricolour image; however, they reported that the methodology lacked repeatability.…”
Section: Total Fringe Order Evaluation Using a Single Imagementioning
confidence: 99%